A Systematic Review of the Effect of Rotavirus Vaccination on Diarrhea Outcomes Among Children Younger Than 5 Years. Issue 9 (September 2016) - Lamberti, Laura M.; Ashraf, Sania; Walker, Christa L. Fischer; Black, Robert E.
Abstract : Background: Rotavirus is the leading cause of vaccine-preventable diarrhea among children under 5 globally. Rotavirus vaccination has been shown to prevent severe rotavirus infections with varying efficacy and effectiveness by region. Methods: We sought to generate updated region-specific estimates of rotavirus vaccine efficacy and effectiveness. We systematically reviewed published vaccine efficacy and effectiveness studies to assess the region-specific effect of rotavirus vaccination on select diarrheal morbidity and mortality outcomes in children under 5 years of age. We employed meta-analytic methods to generate pooled effect sizes by Millennium Development Goal region. Results: Rotavirus vaccination was both efficacious and effective in preventing rotavirus diarrhea, severe rotavirus diarrhea and rotavirus hospitalizations among children under 5 across all regions represented by the 48 included studies. Efficacy against severe rotavirus diarrhea ranged from 90.6% [95% confidence interval (CI): 82.3–95.0] in the developed region to 88.4% (95% CI: 67.1–95.9) in Eastern/Southeastern Asia, 79.6% (95% CI: 71.3–85.5) in Latin America and the Caribbean, 50.0% (95% CI: 34.4–61.9) in Southern Asia and 46.1% (95% CI: 29.1–59.1) in sub-Saharan Africa. Region-specific effectiveness followed a similar pattern. There was also evidence of vaccine efficacy against severe diarrhea and diarrheal hospitalizations. Conclusion: Our findings confirm the protective efficacy and effectiveness of rotavirus vaccination against rotavirus diarrheal outcomes among children under 5 globally. Abstract : Supplemental Digital Content is available in the text.